Green Synthesis of Trifluoromethanesulfonyl Fluoride as an Eco-Friendly Alternative to SF6 Gas Insulation and Analysis of Its Acute Inhalation Toxicity - Shile Wang; Li Dong; Ruichao Peng; Hongding Tang (Molecules)
This study demonstrates an eco-friendly synthesis of trifluoromethanesulfonyl fluoride (TFSF) as a sustainable SF6 alternative. Optimized halogen exchange reactions using CF3SO2Cl/KF (3:1 ratio) with crown ether catalysis at low temperatures achieved 65% TFSF yield (97.9% purity). Scale-up trials in pressurized reactors showed >50% conversion and >90% selectivity. Acute inhalation tests (OECD standards) on Sprague-Dawley rats revealed transient toxicity at 20,000 ppm (4 h exposure), with survival rates >66% and LC50 exceeding 22,600 ppm—significantly safer than SF6. These findings confirm TFSF’s technical viability and low toxicity, positioning it as a practical insulating medium to curb SF6 emissions. The methodology highlights precision halogen exchange control and systematic safety validation, offering actionable solutions for industrial adoption.